Analysis Usage Behavior for Information System of University Library - Gabriel Wahyu Purnomo; Kurniasih Yuni Pratiwi; Kethy Hariyadi Putri (Universitas Pendidikan Indonesia (UPI), 2022)
This research is motivated by the use of university library information systems by users, which affects the behavior of using information systems in the University of Brawijaya Library. In order for library services to run well and experience an increase in users, the information system used must also be accepted and used properly by its users. With the use of information technology is expected to help facilitate service activities in the university library. By using the UTAUT (Unified Theory of Acceptance and Use of Technology) model as an analytical tool, it is expected to know how much influence the usage behavior information System has. This study aims to determine and analyze the effect of the Usage Behavior Information System of the University of Brawijaya Library, the results of which can be used for the development of the information system of the University of Brawijaya Library. The research method used is a quantitative method with a descriptive approach. The results of the study indicate that the use of the university library information system greatly influences the Usage Behavior Information System. However, the moderating effect of age, gender, and experience did not have a significant effect.